TEACHING WRITING BY USING PEER EXCHANGE TECHNIQUE - Vita Vendityaningtyas (Universitas PGRI Madiun, 2013)
Writing is commonly considered as the most difficult skill to learn. It is due to the skills involved in writing, which are highly complex. A learner has to be aware of higher level skills of planning and organizing as well as the lower one of spelling, word choice, punctuation, and so on. Students also need interaction with others to gain more views or ideas.Peer exchange is a technique which allows a teacher to ask students to read one another’s papers and to write feedback notes. It will be useful to arrange students to help one another to improve their written work. This technique is believed to be able to accommodate the students’ need of interaction and get feedback from others that finally will stimulate them to think more critically to make their own written work.This technique itself works in such a way: (1) teacher asks the students to take the paper they have written and pass it to someone else; (2) students keep the papers face down, until teacher commands them to do so; (3) when the teacher commands them ―Go ahead!‖ students are to look over the papers and to provide some written feedback: things they feel interested about the paper; suggestions for improvement; questions; or any other constructive idea; and (4) teacher reminds the students that the goal is to help the person do much better than he already didPeer exchange is believed to be useful in writing activity for it is able to: (1) get all students look over others’ work so they will know some works done better than theirs; (2) perform active learning highly; (3) provide lot of feedback to students very efficiently than teacher alone could provide.